1996
DOI: 10.3109/08958379609005442
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pulmonary Inflammatory Response to Ozone During Lactation in Rats: Evaluation of the Influence of Inhaled Dose

Abstract: We previously demonstrated that rats in a late stage of pregnancy and throughout lactation were more susceptible to pulmonary inflammation induced by exposure to 1 ppm ozone than were age-matched virgin females or rats following lactation. The purpose of the study reported here was to extend the comparison of ozone-induced pulmonary inflammation in lactating and postlactating rats to lower concentrations of ozone and to investigate the hypothesis that the enhanced response demonstrated by lactating rats is att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The changes in pressure are due to gas compression from breathing mechanics of the animal and gas conditioning from heating and humidification of inspired air, with the gas conditioning being the predominate source for the pressure change (Lundblad et al, 2002;Mitzner & Tankersley, 1998). This method has been used by previous researchers (Kimmel et al, 2002;Mortola & Seifert, 2002;Seifert & Mortola, 2002a, 2002b, 2002cStrohl et al, 1997;Tankersley et al, 1997;Weideman et al, 1996) to measure respiratory parameters in small animals. The technique is advantageous because it is noninvasive and nonstressful, thus allowing repetitive monitoring of the same rats over the entire period of gestation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The changes in pressure are due to gas compression from breathing mechanics of the animal and gas conditioning from heating and humidification of inspired air, with the gas conditioning being the predominate source for the pressure change (Lundblad et al, 2002;Mitzner & Tankersley, 1998). This method has been used by previous researchers (Kimmel et al, 2002;Mortola & Seifert, 2002;Seifert & Mortola, 2002a, 2002b, 2002cStrohl et al, 1997;Tankersley et al, 1997;Weideman et al, 1996) to measure respiratory parameters in small animals. The technique is advantageous because it is noninvasive and nonstressful, thus allowing repetitive monitoring of the same rats over the entire period of gestation.…”
Section: Discussionmentioning
confidence: 98%
“…Gunnison et al (1992) noted significantly enhanced sensitivity to ozone-induced pulmonary inflammation in rats during pregnancy and lactation. The enhanced sensitivity may be due to higher ozone delivery in the pulmonary region of the lung resulting from increased ventilation (Gunnison & Hatch, 1999;Weideman et al, 1996).…”
mentioning
confidence: 98%
“…It is clear from previous studies that lactating and pregnant rats (17 days gestation) suffer approximately equivalent pulmonary inflammation and damage following acute ozone exposure and that these pulmonary effects are much greater than those exhibited by virgin female or postlactating rats after identical exposures [4,5,22]. Data from the current study show that there is a small, progressive decrease in the overall concentration of fatty acid double bonds detected in the surfactant and membrane phospholipids of lung tissue during pregnancy and lactation relative to virgin female rats.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that lactating rats and rats in a late stage of pregnancy are significantly more sensitive to inhaled ozone than are virgin female or postlactating rats [4,5,22] Fatty acids are known to be mobilized from fat stores late in pregnancy, resulting in high circulating levels of free fatty acids [8,11] and presenting an opportunity for the remodeling of the fatty acid composition of tissue phospholipids. Since phospholipid fatty acids (PLFAs) are ostensibly common molecular targets for ozone that are responsible for initiating toxic responses, it seems feasible that the pulmonary inflammatory response might be altered by changes in the composition of phospholipid fatty acid molecules available for reaction with ozone in the milieu of the lung surface.…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that in this animal model prolactin did not significantly elevate airway PMN inflammation induced by ozone, and supplementation with exogenous glucocorticoid did not duplicate the endogenous airway PMNs numbers observed in MMQ r -bearing rats or lactating rats, c IW society or Ozone is a photochemical oxidant that has been shown to cause decrements in pulmonary function, inhibition of host defenses against inhaled infectious agents, and pulmonary inflammation at concentrations existing in community air (U.S. Environmental Protection Agency, 1996). Recently, pregnancy and lactation have been identified as physiological states that are sensitive to acute ozone exposure (Gunnison et al, 1992Weideman et al, 1996). Specifically, ozone-induced pulmonary inflammation in rats was found to be more severe in late pregnancy (Day 17 of gestation) and throughout lactation than in early to midpregnancy (Day 10 of gestation), following lactation, or in age-matched cycling females (Gunnison et al, 1992).…”
mentioning
confidence: 99%